Cytokines and intestinal inflammation. Issue 6 (November 2016) - Bamias, Giorgos; Cominelli, Fabio
Abstract : Purpose of review: Cytokines of the intestinal microenvironment largely dictate immunological responses after mucosal insults and the dominance of homeostatic or proinflammatory pathways. This review presents important recent studies on the role of specific cytokines in the pathogenesis of intestinal inflammation. Recent findings: The particular mucosal effects of cytokines depend on their inherent properties but also the cellular origin, type of stimulatory antigens, intermolecular interactions, and the particular immunological milieu. Novel cytokines of the interleukin-1 (IL-1) family, including IL-33 and IL-36, have dominant roles in mucosal immunity, whereas more established ones such as IL-18 are constantly enriched with unique properties. Th17 cells are important mucosal constituents, although their profound plasticity, makes the specific set of cytokines they secrete more important than their mere numbers. Finally, various cytokines, such as tumor necrosis factor-α, IL-6, tumor necrosis factor-like cytokine 1A, and death receptor, 3 demonstrate dichotomous roles with mucosa-protective function in acute injury but proinflammatory effects during chronic inflammation. Summary: The role of cytokines in mucosal health and disease is increasingly revealed. Such information not only will advance our understanding of the pathogenesis of gut inflammation, but also set the background for development of reliable diagnostic and prognostic biomarkers and cytokine-specific therapies.